(untitled) (Homoeopathy for All, 2026)
The term “Allergy” was coined by an Austrian paediatrician named Clemens von Pirquet in 1906 and has its roots derived from two Greek words namely allos ("other" or "different") and ergon ("activity" or "reaction"). It is described as an exaggerated response of the immune system to foreign substances that get inside the body. These foreign bodies are usually harmless substances such as pollens, food, dust, insects, ticks, moulds and drugs which are termed as Allergens.